TNF-alpha rs1800629 polymorphism is not associated with HPV infection or cervical cancer in the Chinese population. - Ning Wang; Duo Yin; Shulan Zhang; Heng Wei; Shizhuo Wang; Yang Zhang; Yanming Lu; Shuyan Dai; Wei Li; Qiao Zhang; Yao Zhang (PLoS ONE, 2012)
BACKGROUND: While HPV infection is the main cause of cervical cancer, genetic susceptibility to HPV infection is not well understood. Tumor necrosis factor alpha (TNF-alpha), involved in the defense against HPV infection, plays an important role in cervical cancer progression and regression. The aim of this study was to investigate the relationship between the TNF-alpha rs1800629 polymorphism and risk of HPV infection or cervical cancer. METHODS: Three groups were involved in this study of Chinese women. Group 1 consisted of 285 high risk HPV positive cervical cancer patients, Group 2, 225 high risk HPV positive patients without cervical cancer, and Group 3, 318 HPV negative women with no cervical cancer. Blood samples were obtained from all patients and genotyped by PCR-RLFP. Fifty randomly selected samples were further sequenced. RESULTS: The allele and genotype distributions of the TNF-alpha rs1800629 polymorphism were not significantly different between each of the groups (P>0.05). There are no significant relationship between rs1800629 polymorphism and high risk HPV infection (OR = 0.649, 95% CI: 0.253-1.670, P = 0.371), cervical cancer (OR = 0.993, 95% CI: 0.376-2.618, P = 0.988), or cervical cancer with HPV infection (OR = 0.663, 95% CI: 0.250-1.758, P = 0.409). CONCLUSIONS: We demonstrated that there is no association between TNF rs1800629 polymorphism and the HPV infection, or cervical cancer with HPV infection.